Simulation-based Team Training for Multiprofessional Obstetric Care Teams to Improve Patient Outcome: A Multicentre, Cluster Randomized Controlled Trial. Issue 4 (December 2017) - Fransen, A.F.; van de Ven, J.; Schuit, E.; van Tetering, A.A.C.; Mol, B.W.; Oei, S.G.
Abstract : ( BJOG . 2017;124:641–650) Simulation training is considered an important component in medical education. It provides a more effective method for teaching technical skills through practice without risk to the patient. It has also been recommended for obstetric teams as a way to improve team performance and perhaps obstetric outcomes. Criteria for assessing simulation training has included participants' perceptions of the simulation experience, assessment of knowledge and skills during and after simulation, subsequent changes in clinical practice, and ultimately improvement in patient outcomes. However, data on the effect of simulation training on patient outcomes has been limited. This study looked at the effect of a 1-day simulation-based training course for obstetric teams on the rate of patient complications over a 1-year period.